2011
DOI: 10.1111/j.1469-7610.2011.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

Do callous-unemotional traits moderate the relative importance of parental coercion versus warmth in child conduct problems? An observational study

Abstract: These findings suggest that different dimensions of parenting may need to be targeted in the treatment of early onset conduct problems in children high and low on CU traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
180
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(208 citation statements)
references
References 45 publications
21
180
6
1
Order By: Relevance
“…Consistent with a growing literature showing that positive parenting-including warmth, responsivity, and praise-predict callous-unemotional behaviors, and this type of gene-environment interaction suggests that parent-child temperament pathways could also be moderated by caregiving quality [116,156].…”
Section: Prognosissupporting
confidence: 52%
See 3 more Smart Citations
“…Consistent with a growing literature showing that positive parenting-including warmth, responsivity, and praise-predict callous-unemotional behaviors, and this type of gene-environment interaction suggests that parent-child temperament pathways could also be moderated by caregiving quality [116,156].…”
Section: Prognosissupporting
confidence: 52%
“…Studies examining these aspects of negative parenting practices are more strongly related to conduct problems in those low on CU traits. Speciically, harsh, inconsistent, and coercive discipline has consistently been shown to be more highly associated with conduct problems in youths with normative levels of CU traits [114][115][116]. In the studies, it is found that chronically elevated levels of callousness have been longitudinally related to harsh parenting in children aged 2-4 years [117], as well as poor parent-child communication among male adolescents with symptoms of ODD/CD [118].…”
Section: Parenting and Environmental Factorsmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, in a sample of 9-10 year-olds, Yeh and colleagues (Yeh, Chen, Raine, Baker, & Jacobson, 2011) found that children's reporting of both positive and negative parenting were more strongly associated with self-reported reactive aggression in children with low versus high levels of psychopathic traits. A study of young clinic-referred children (Pasalich, Dadds, Hawes, & Brennan, 2011) found that coercive parenting was more strongly associated with conduct problems in children with low compared with elevated levels of CU; other studies suggest that disciplinary practices may be more weakly associated with behavioral problems in children with elevated CU traits (Oxford, Cavell, & Hughes, 2003;Wootton, Frick, Shelton, & Silverthorn, 1997). A third line of evidence is from intervention studies showing that CU traits may be associated with weaker perceived response to punishment such as time-out (Hawes & Dadds, 2007), and that children with elevated CU traits may be less responsive to intervention (Spain, Douglas, Poythress, & Epstein, 2004).…”
Section: Observational and Experimental Findingsmentioning
confidence: 99%